An Experimental Study on the Slippage Effects of Sandstone under Confining Pressure and Low Pore Pressure Conditions. (24th February 2020) - Li, Zhengdai; Zuo, Jianping; Shi, Yue; Xu, Fei; Yu, Meilu; Mi, Changning
Abstract : Due to the influences of various factors, such as temperature, stress, and composition, the research regarding rock permeability has been complicated. This study examined the variation laws of sandstone specimens under changing rates of confining and pore pressures after high-temperature heat treatments. The results showed that the free water in the rock volatilized during the low-temperature heat treatments in the range of 100°C to 300°C, with the increase of the heat-treatment temperature above 500°C; the crystal water in the rock is gradually separated out; and the particles in the samples had undergone phase transformations resulting in increased permeability. According to ultrasonic wave velocity test results, the internal cracks of the samples expanded with the increases in the heat-treatment temperatures. In addition, the high-temperature heat treatments were found to improve the accuracy of the direction of the Earth's stress when using circumferential wave velocity anisotropy methods. Under the influence of slippage effects, as the pore pressure increased, the measured permeability of the samples decreased and the slippage effect occurs in the rock samples with the permeability of 10 -3 μ m 2 10 -6 μ m 2 . The experimental results showed that the contribution rate of the slippage effect decreases with the increase of the heat-treatment temperature of the specimen, and the contribution rates of the sandstone slippage effect were generally higher than 5%. Therefore, the impact effects on the permeability of sandstone slippage should be considered in practical engineering processes.